2017
DOI: 10.1371/journal.pone.0175495
|View full text |Cite
|
Sign up to set email alerts
|

A flavone-polysaccharide based prescription attenuates the mitochondrial dysfunction induced by duck hepatitis A virus type 1

Abstract: The principal target organ of duck hepatitis A virus type 1 (DHAV-1) is duckling liver, which is an energy-intensive organ and plays important roles in body’s energy metabolism and conversion. As the “power house” of the hepatocytes, mitochondria provide more than 90% of the energy. However, mitochondria are much vulnerable to the oxidative stress for their rich in polyunsaturated fatty acids. Although previous researches have demonstrated that DHAV-1 could induce the oxidative stress in the serum of the infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Therefore, we hypothesized that a similar phenomenon occurred in the livers of DHAV-1-infected embryonated eggs. Moreover, the mitochondria in the livers of the CH60 group were slightly swollen where the ridge was fractured (Figure 2 ), which was consistent with mitochondrial injury in ducks infected with DHAV-1 ( 40 ). The mitochondrial apoptosis pathway is the main pathway of apoptosis, and damaged mitochondria are likely to affect apoptosis ( 41 , 42 ).…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, we hypothesized that a similar phenomenon occurred in the livers of DHAV-1-infected embryonated eggs. Moreover, the mitochondria in the livers of the CH60 group were slightly swollen where the ridge was fractured (Figure 2 ), which was consistent with mitochondrial injury in ducks infected with DHAV-1 ( 40 ). The mitochondrial apoptosis pathway is the main pathway of apoptosis, and damaged mitochondria are likely to affect apoptosis ( 41 , 42 ).…”
Section: Discussionsupporting
confidence: 68%
“…On the contrary, Cat activities decrease slightly during the same period in both sexes. An increase in SOD and Cat activities has often been described under different conditions (Zeng et al, 2014;Liu et al, 2015;Du et al, 2017;Zhang et al, 2017;Remignon and Burgues, 2023) to be associated to fight against oxidative stress due to the accumulation of lipids in hepatocytes. However, in mice fed a cafeteria diet, Gasparin et al (2018) reported decreased Cat activity in the liver and indicated that this suggests impaired H 2 O 2 neutralization that could contribute to lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that force-feeding induced rapidly an oxidative stress in liver cells but the constancy of the SOD/Cat ratio also indicates that no major dysregulation of these coupled activities is present. In different pathological 20,21 or feeding 22 or environmental conditions 23 , the activities of SOD and Cat enzymes also increase to reduce the oxidative stress and are therefore considered to be one of the predominant antioxidant mechanisms in duck hepatocytes. Other enzymatic antioxidant systems (GPX1 and NQO1) activities are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%